Effects of transcutaneous auricular vagus nerve stimulation combined with repetitive facilitative exercise on lower limb motor function in patients with intracerebral hemorrhage: A pilot randomized controlled trial - Hanji Chen; Hanbo Chen; Chongrui Feng; Jiafa Liu; Xiaoli Li; Gengbiao Zhang; Zhanhao Liu; Mengyun Li (PLoS ONE, 2026)
Objective To evaluate the clinical efficacy of transcutaneous auricular vagus nerve stimulation (taVNS) combined with repetitive facilitative exercise (RFE) in improving lower limb function in patients with intracerebral hemorrhage. Methods The research protocol was registered on the Chinese Clinical Trial Registry website (ChiCTR2500106064). Sixty patients with intracerebral hemorrhage were randomly assigned to either the experimental group (n = 30) or the control group (n = 30). The experimental group received real taVNS combined with RFE, while the control group received sham taVNS combined with RFE. Before and after 6 weeks of treatment, functional assessments were conducted using the Fugl-Meyer Assessment-Lower Extremities (FMA-LE), the Functional Ambulation Category (FAC) scale, and a three-dimensional gait analysis system to obtain kinematic parameters of the pelvis during the walking cycle. Results Baseline demographic and clinical characteristics showed no significant differences between the two groups (all P > 0.05). After 6 weeks of intervention, both groups exhibited significant improvements in FMA-LE, FAC, stride length, peak hip extension angle, and peak hip joint moments (all P < 0.05). However, the experimental group demonstrated superior outcomes compared to the control group in FMA-LE (t = 3.233, P = 0.002), FAC (t = 2.868, P = 0.006), stride length (t = 3.077, P = 0.003), and peak hip extension angle (t = 2.682, P = 0.010). No significant difference was observed in peak hip joint moments (t = −0.212, P = 0.833) between the two groups after treatment. No adverse effects or dropouts were reported during the study. Conclusion Compared to sham taVNS combined with RFE, taVNS combined with RFE can significantly enhances lower limb motor function in patients with post-stroke hemiplegia following intracerebral hemorrhage. The research protocol has been registered on the Chinese Clinical Trial Registry website ( ChiCTR2500106064 ).